Oxidative stability of olive oil after food processing and comparison with other vegetable oils - Lisete Silva (2010)
The use of olive oil showed an important protection of meat and potatoes when compared with other vegetable oils, with sunflower oil samples being oxidised after 60 min of processing at 180 C. Olive oil samples were not oxidised. independently of the olive oil quality used. Shelf life was longer for extra-virgin olive oil containing samples and this fact was positively correlated with their higher phenolic content. The radical-scavenging activity of extra-virgin olive oil was higher than for other olive oil samples and was also positively correlated with the phenolic content of the oil. Seed oil antioxidants showed little capacity in delaying the oxidative degradation of seed oils and meat processed with them. However, tocopherol content and the identity of tocopherols present in the oil were shown to have a more important role in the oxidative stability of seed oils than the fatty acid composition. The presence of food showed a protective effect on the oils, with oil samples processed without food showing a higher level of oxidation than the oil samples processed in the presence of food. All polyphenolic components of olive oils decreased in concentration with the thermal treatment and this decrease was dramatic in the presence of food. During processing, two new compounds were found in olive oil samples and their concentration was higher for samples containing a higher initial polyphenolic content. The content in tocopherols was not so dramatically affected by the thermal treatment as was the polyphenolic content. Moreover, a sparing effect of food was, however, observed with the tocopherol content of samples which probably contributes to the better oxidative stability of these samples.